Satisfaction and comparison income in transition and developed economies - DUMLUDAĞ, DEVRİM (Springer Verlag, 2014)
The main purpose of this paper is to evaluate the impact of different types of income comparison on subjective well-being in transition countries and developed European countries. The paper relies on the Life in Transition Survey (European Bank for Reconstruction and Development 2011), which was conducted in late 2010 jointly by the European Bank for Reconstruction and Development and the World Bank. The emphasis of the paper is on income comparisons, specifically; local comparisons and self-ranking. The main findings reveal that comparisons have a significant impact on life satisfaction in transition countries, whereas the relationship between comparison and life satisfaction is ambiguous in developed European countries. In transition countries, the impact of comparisons is asymmetric: in most cases, under-performing one's benchmark has a greater effect than out-performing it. In transition countries, both downward and upward evaluations have an impact on life satisfaction, while it is worthy of note that all upward evaluations have no effect on life satisfaction in developed European countries. © 2014 Springer-Verlag Berlin Heidelberg.
Keywords: Economic development; Income comparisons; Life satisfaction; Transition countries